Hubungan Self Efficasy dan Motivasi dengan Pemahaman Konsep IPA Terpadu Siswa Kelas VIII SMP Pertiwi 2 Padang - Reni Nastuti; Lelfita Lelfita; Elbasthoh Elbasthoh (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The research aims to describe 1.The relationship of self-efficacy and the students understanding of the concept of Pertiwi 2 Junior High School Padang. 2. The relationship of motivation and the understanding of the concept of Pertiwi 2 Junior High School students. Factors that can influence a student's understanding of concept are not only depend on the media, model, strategy and learning environment but depend on the students themselves which are self efficacy and motivation. The research is begun at the beginning of the even semester of 2017/2018 academic year. The population in this study was eight (VIII) grade students of Pertiwi 2 Junior High School Padang. The variables consisted of self efficacy (X1), motivation (X2) and understanding of concept (Y). The sample used random sampling which totaled 52 samples. The type of research is descriptive research. The instrument used in this study is questionnaire. The essay as a test is given at the end of Science study to find out the students level of understanding concepts. Based on the data analysis self efficacy 0.184 in the lowest relationship level. According to the significance test, was used t test, in real level = 0,05 with degree of freedom (dk=44) was obtained ttable 1,68. Based on the criteria of the test, ttable = 1.68 and t count = 1.243. Means Hi was rejected and H0 was accepted. The motivation relationship level is 0.089 in the lowest level. Based on the significance test, was used t test, in real level = 0,05 with degree of freedom (dk=44) was obtained ttable 1,68. The tests criteria result is ttable =1,68 dan t count =0.593. Means Hi is rejected and H0 was accepted. So, it can be concluded as there is no significant relationship of self efficacy and motivation with the understanding of concepts of integrated science in VIII class of Pertiwi 2 Junior High School Padang.